Dose-Dependent Neuroprotective Effect of Standardized Bee Venom Phospholipase A2 Against MPTP-Induced Parkinson’s Disease in Mice - Kim, Kyung Hwa; Lee, Seung Young; Shin, Jaekwon; Hwang, Jae-Taeg; Jeon, Hat Nim; Bae, Hyunsu (Frontiers in Aging Neuroscience, 2019)
Parkinson’s disease (PD) is a chronic progressive neurodegenerative movement disorder characterized by the selective loss of dopaminergic neurons within the substantia nigra (SN). While the precise etiology of dopaminergic neuronal demise is elusive, multiple lines of evidence indicate that neuroinflammation is involved in the pathogenesis of PD. We have previously demonstrated that subcutaneous administration of bee venom phospholipase A2 (bvPLA2) suppresses dopaminergic neuronal cell death in a PD mouse model. In the present study, we established standardized methods for producing bvPLA2 agent isolated from crude bee venom at good manufacturing practice (GMP) facility. The therapeutic efficacy of purified bvPLA2 agent was examined in MPTP-induced PD mice. Importantly, administration of purified bvPLA2 in a dose-dependent manner reversed motor deficits in PD mice as well as inhibited loss of dopaminergic neurons within the SN of PD mice. The concentration-dependent action of standardized bvPLA2 appeared to be related to the induction of CD4+CD25+Foxp3+ regulatory T cells (Tregs), which, in part, inhibits T helper 1 (Th1) and Th17 polarization and suppresses microglial activation in PD mice. Taken together, these results suggest that standardized bvPLA2 purified from bee venom shows neuroprotective effect against PD and thus has a potential target for treatment of PD.